2022
DOI: 10.1021/acs.jpca.2c00907
|View full text |Cite
|
Sign up to set email alerts
|

KiMoPack: A python Package for Kinetic Modeling of the Chemical Mechanism

Abstract: Herein, we present KiMoPack, an analysis tool for the ki netic mo deling of transient spectroscopic data. KiMoPack enables a state-of-the-art analysis routine including data preprocessing and standard fitting (global analysis), as well as fitting of complex (target) kinetic models, interactive viewing of (fit) results, and multiexperiment analysis via user accessible functions and a graphical user interface (GUI) enhanced interface. To facilitate its use, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 77 publications
1
46
0
Order By: Relevance
“…To our knowledge, this is the first demonstration of utilizing a powerful and highly versatile tool for the analysis of disparate, simultaneously desorbing and adsorbing species. This substantiates the potential for future developments using global and target analyses, including higher-order and even deep-learning analyses, tailored to specific NEMS-IR-TD applications. Therefore, we expect that this technique will find a wide range of applications for the physicochemical characterization of complex samples in various fields from environmental analysis to life sciences.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…To our knowledge, this is the first demonstration of utilizing a powerful and highly versatile tool for the analysis of disparate, simultaneously desorbing and adsorbing species. This substantiates the potential for future developments using global and target analyses, including higher-order and even deep-learning analyses, tailored to specific NEMS-IR-TD applications. Therefore, we expect that this technique will find a wide range of applications for the physicochemical characterization of complex samples in various fields from environmental analysis to life sciences.…”
Section: Discussionsupporting
confidence: 68%
“…Both the spectral and mass data can be obtained from the frequency detuning of the NEMS resonator. The resulting time-resolved IR spectra can readily be decomposed by singular value decomposition (SVD) and a global analysis adapted from the field of ultrafast spectroscopy. Additionally, the mass data allow for the simultaneous study of the components’ desorption dynamics as has been demonstrated with NEMS paddle resonators or surface acoustic wave detectors . As a demonstration of NEMS-IR-TD, binary mixtures of two chemically similar compounds, caffeine and theobromine, were analyzed with limits of detection of 5.7 and 4.9 pg, respectively (∼30 fmol).…”
mentioning
confidence: 99%
“…The kinetics for [Fe(meophtmeimb) 2 ]PF 6 and [Fe(coohphtmeimb) 2 ]PF 6 are similar (see Supporting Information Figures S24 and S25 ). The excited state decay can be accurately described by a single exponential model and a global fit 36 to the data resulting in a universal lifetime of ∼2 ns at all observed features and for all [Fe(phtmeimb) 2 ]PF 6 derivatives; see Table 4 . These results are in good agreement with emission lifetimes (of 1.9 ns) determined by time-correlated single photon counting (TC-SPC, in Supporting Information section S10, Figure S27, and Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The probe pulses are recollimated and spectrally dispersed by a prism and detected by a diode array (Pascher Instruments AB, readout frequency of 1 kHz). The fs‐TA data was analysed using the KiMoPack tool [47] . Prior to global lifetime analysis the data was arrival‐time corrected.…”
Section: Methodsmentioning
confidence: 99%
“…The fs‐TA data was analysed using the kimopack tool. [47] Prior to global lifetime analysis the data was arrival‐time corrected. The temporal resolution was limited to 0.3 ps, to avoid strong contributions of coherent artefacts to the signals.…”
Section: Methodsmentioning
confidence: 99%